2021
DOI: 10.3390/ijms222312662
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Peptides: From Design to Biomedical Applications

Abstract: Self-assembling peptides could be considered a novel class of agents able to harvest an array of micro/nanostructures that are highly attractive in the biomedical field. By modifying their amino acid composition, it is possible to mime several biological functions; when assembled in micro/nanostructures, they can be used for a variety of purposes such as tissue regeneration and engineering or drug delivery to improve drug release and/or stability and to reduce side effects. Other significant advantages of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 157 publications
0
41
0
Order By: Relevance
“…As follows from Table 1, the distance between spin labels increases to about 0.9-1.2 Å in the presence of divalen This value is less than the translation per amino acid of a α-helix (1.5 Å). If we r assume the peptide structure to be a mixture of just two helix types (310 and 2. observed change in the mean spin-spin distance would increase by a shift in the tion point' between the two helices by only one amino acid residue [16,26]). Thus, There are two possible reasons why the changes in the dipolar signals in the timedomain are so weak: (i) the intrinsic, short length of the peptide trichogin results in TOAC-TOAC distances close to the lower limit of the DEER method resolution [54,56,58]; (ii) the relatively small ion-induced distance change, in respect to the original TOAC-TOAC distance.…”
Section: Pulse Epr Datamentioning
confidence: 96%
See 2 more Smart Citations
“…As follows from Table 1, the distance between spin labels increases to about 0.9-1.2 Å in the presence of divalen This value is less than the translation per amino acid of a α-helix (1.5 Å). If we r assume the peptide structure to be a mixture of just two helix types (310 and 2. observed change in the mean spin-spin distance would increase by a shift in the tion point' between the two helices by only one amino acid residue [16,26]). Thus, There are two possible reasons why the changes in the dipolar signals in the timedomain are so weak: (i) the intrinsic, short length of the peptide trichogin results in TOAC-TOAC distances close to the lower limit of the DEER method resolution [54,56,58]; (ii) the relatively small ion-induced distance change, in respect to the original TOAC-TOAC distance.…”
Section: Pulse Epr Datamentioning
confidence: 96%
“…This value is less than the translation per amino acid of a α-helix (1.5 Å). If we roughly assume the peptide structure to be a mixture of just two helix types (3 10 and 2.2 7 ), the observed change in the mean spin-spin distance would increase by a shift in the 'transition point' between the two helices by only one amino acid residue [16,26]). Thus, neither a subtle change in the type of helix nor a possible bidentate coordination of metal ions by the main peptide chain are enough to explain the observed peptide selectivity towards ions.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The building blocks of peptides are amino acids [56]. They also suggested that amino acid side chains with a terminal -COOH or -NH 2 can be placed [16]. stated that there is a controlled interaction between adjacent peptides [17], and this interaction can self-organise into different structures [56].…”
Section: P11-4 Self-assembling Peptidementioning
confidence: 99%
“…The self-assembling peptide was first discovered in 1989 due to curiosity-driven research similar to the chance discovery of X-ray and CRISPR for gene editing [15]. Since then, self-assembling peptides have been used in an array of applications ranging from surfactant materials to accelerated wound healing in regenerative medicine [15,16].…”
Section: Introductionmentioning
confidence: 99%